Influence of Formalization on Role Stress, Organizational Commitment, and Work Alienation of Salespersons: A Cross-National Comparative Study - Agarwal, Sanjeev (Journal of International Business Studies, 1993)
Organizations rely on formalization to coordinate the efforts of employees; however, this practice has been found to have a negative influence on role stress, organizational commitment, and work alienation of salespersons. Though the negative influence of formalization in the United States has been known for some time, we still cannot predict if similar relationships would/should be observed in other countries because the rationale developed to explain these relationships in the United States did not consider the cultural factors that influence them. With such knowledge, it would become possible to anticipate the nature of the relationship in different cultural environments. Such an approach to developing cross-national models has been often suggested but seldom implemented. By emphasizing the role of culture, this study generates practical guidelines for both practitioners and theorists.